PENERAPAN MEDIA BERBANTUAN APLIKASI CANVA UNTUK MENINGKATKAN HASIL BELAJAR PKn KELAS VIII SMPN 38 MALUKU TENGAH - Maria Silvya Kapitan; Ridwan Hatala; Aisa Abas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to find out how to apply media assisted by the Canva application to improve Civics learning outcomes for class VIII students at SMP Negeri 38 Central Maluku. Quantitative method research type or Classroom Action Research (PTK). From the results of this research, it can be concluded that the application of media assisted by the Canva application to improve students' Civics learning outcomes in class VIII at SMPN 38 Central Maluku is: 1) The teacher carries out apperception by providing a video that is broadcast using the Canva application for students to view and the students provide feedback regarding in the video, 2) The teacher divides the students into several groups to solve the problems given by the teacher, 3) The teacher gives students to discuss to solve the problems given, 4) The teacher gives the students the opportunity to present problems that have been successfully solved, 5) The teacher provides reinforcement and conclusions about the results found and the material taught. This research also shows that there is an increase with the application of media assisted by the Canva application in learning. This can be seen from the increase in the results of cycle I, cycle II and cycle III. In the results of the first cycle, the average student score was 65.3, 7 students who achieved completeness had a percentage of 20%, while 23 students who had not completed it had a percentage of 80%. In cycle II the average student score was 75.3%, students who had completed 50% with a total of 15 students and the remaining students who had not completed were also 15 students with a percentage of 50%. Meanwhile, in cycle III the average student score was 84.6%, students who completed it were 96.7% with a total of 29 students and 1 student who had not completed it with a percentage of 3.3% due to not attending school/Alpa. Thus, this classroom action research was completed in cycle III and did not continue in subsequent cycles.